Danmari kōrogi mushi no ne ga kikoeru hon - Carle, Eric 1929-2021 (Kaiseisha, 2016)
A very quiet cricket who wants to rub his wings together and make a sound as do so many other animals finally achieves his wish. The cricket's sound is reproduced at the end of the book